Temperature and Machine Speed Settings to Reduce Defects Products in the Glass Bottle Washing Process - Ragil Pardiyono; Akbar Rizky Fatullah (Universitas Ahmad Dahlan Indonesia, 2021)
Surabraja food trading company produces chili sauce and soy sauce. In July 2019, this company suffered a loss due to the number of broken bottles in the bottle washing process amounting to IDR 29,597,400. This study will identify the causes of defects using the six sigma method. Based on the define, measure, and analyze stages, it was found that the main causes of broken bottle defects were the temperature setting that was too hot and the engine speed that was not optimal. The repair process uses the taguchi experiment by determining the temperature and speed settings. The results of the Taguchi experiment showed that the best selected setting dosage formulations and their levels were A1 and AB2 where A1 (temperature 140°C), and AB2 (speed 10,000 bph). Based on a confirmation experiment with a temperature setting of 140°C, and a speed setting of 10,000 bpd, it was carried out using 48,000 bottles with 5 experiments, and a defect of 505 bottles was obtained. The results of the study concluded that the best results, namely at a temperature of 140°C and a speed of 10,000 bpd, can reduce the defect rate from 780 bottles to 505 bottles per day, and the value of the company's losses from IDR 466,429, - to IDR 301,900, -.